Safety Bundle for Severe Hypertension During Pregnancy and Postpartum. Issue 3 (May 2018) - Wisner, Kirsten
Abstract : Hypertensive disorders of pregnancy are a leading contributor to maternal morbidity and mortality. Our maternity nursing expert, Kirsten Wisner, highlights the new patient safety bundle on severe hypertension during pregnancy and postpartum released by the National Partnership for Maternal Safety in 2017.